The Impact of Digitalization on the Transformation of Management Accounting: A Cross-Sector Study in Indonesia - Husni Mubarok; Lierni Simarmata; Aminah, Siti; Tri Meseri Cordias Waruwu; Muhammad Alfian Prayogi; Rozza Hafilah Masqurun (Wealth: Journal of Islamic Banking and Finance, 2025)
The purpose of this research is to examine the effect of digitalization on management accounting transformation in manufacturing and service industries in Indonesian context. Based on qualitative-descriptive analysis, the study involves three companies from the manufacturing, financial services and digital retail sectors. From companies that have adopted digital technologies (including Enterprise Resource Planning [ERP], Artificial Intelligence [AI], the Internet of Things [IoT] and big data analytics), data were gathered through interviews, observations and analysis of documents. The results indicate that digitalization has had a radical impact on the role of management accounting in planning, forecasting, and controlling. In addition, the digitalization of systems also leads to an improvement in efficiency, transparency, and timeliness of management reporting for data-based decisions. The findings highlight the fact that digital transformation is not only relevant from the technological viewpoint, but also from the strategic one, where management accounting is positioned as a decision- making partner within the industry 4.0 paradigm.